Using attitudes, beliefs, and behaviours to shape a Cambodian motorcycle helmet campaign. (7th October 2012) - Roehler, D; Sann, S; Kim, P; Florian, M; Sidik, M; Ballesteros, M.
Abstract : Background: As the number of motorcyclists in Cambodia increases, so do motorcycle-related injuries. Injuries decrease as helmet use increases. Campaigns addressing this issue will be more effective if they are based on prior knowledge and barrier of helmet use. Aims/Objectives/Purpose: To determine the prevalence of helmet use and reasons for non-use among motorcycle riders in Cambodia. Methods: We conducted helmet observations and roadside interviews in five Cambodian provinces. Results/Outcomes: Trained researchers observed helmet use for drivers of 71.4% at 9:00, 68.2% at noon, 62.7% at 17:00, and 47.8% at 19:00. For passengers, researchers observed rates of 6.6% at 9:00, 7.9% at noon, 6.3% at 17:00, and 4.7% at 19:00. Most drivers and passengers older than 16 years who reported that they regularly wear a helmet said they do so because it can save their life (96% and 98%, respectively). The most common reasons for not consistently wearing a helmet were: (1) 'factors that depend on where I drive, ' (2) 'I forgot', (3) 'inconvenient/uncomfortable'. We found that 91% of riders get their road safety information from the television. Parents reported their children do not regularly wear a helmet because they are 'too young' (37%) or they are 'riding close to home in their neighborhood' (17%). Significance/Contribution to the Field: Helmet use varied greatly between drivers and passengers by time of day. As a result of these data, we have launch a television campaign focused on passengers and emphasising the importance of wearing a helmet anytime they are on a motorcycle.